Effects of Two Palms (Borassus aethiopum Mart and Hyphaene thebaica (L.) Mart) on Soil Physicochemical Properties in the Agroforestry Parklands of Gaya, Niger - Garba Seyni, Abdoulaye; Barron, Vidal; Mounkaïla, Hamissou Amadou; Navajas, Antonio; Villar, Rafael (European Scientific Journal, ESJ, 2025)
This study aims to determine the contribution of B. aethiopum and H. thebaica for improving soil fertility in south-west Niger. For this purpose, a complete randomized experimental design with three replicates was used. A total of 45 composite samples of 100 g of soil (36 below canopy and 9 outside) were collected between 0 and 20 cm depth. The data were used to determine organic matter, total carbon, total nitrogen, total sulfur, macronutrients (Mg, Ca, Na and K), phosphorus and micronutrients (Fe, Zn, Cu and Mn) contents, pH, hygroscopic moisture, electrical conductivity and texture. The results revealed that levels of OM, C, N, Mn, Mg, Zn, HM, P, and Fe are higher beneath the canopies of both palm species, with a more pronounced enrichment observed under B. aethiopum. Except for phosphorus (P), variations in nutrient levels were largely explained by the soil’s organic matter, with which they showed strong and significant correlations. The study demonstrated that B. aethiopum and H. thebaica significantly enhance soil fertility and contribute to its structural stability. In light of these findings, it is crucial to develop policies that promote the rational management of forest resources as a sustainable strategy for preserving agricultural soil fertility.